2020
DOI: 10.1039/c9em00595a
|View full text |Cite
|
Sign up to set email alerts
|

Comparing non-targeted chemical persistence assessed using an unspiked OECD 309 test to field measurements

Abstract: Here we test the hypothesis that unspiked OECD 309 tests can quantitatively predict chemical persistence in the environment by comparing chemical half-lives assessed in the laboratory against those measured in the field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 29 publications
3
13
0
Order By: Relevance
“…This observation is consistent with previous reports of 2,4-D and other polar organic compound degradation in water/sediment systems. The lack of degradation in the water-only microcosms is likely attributable to insufficient biomass compared to sediment-water suspensions. ,, …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This observation is consistent with previous reports of 2,4-D and other polar organic compound degradation in water/sediment systems. The lack of degradation in the water-only microcosms is likely attributable to insufficient biomass compared to sediment-water suspensions. ,, …”
Section: Resultsmentioning
confidence: 99%
“…Understanding the environmental fate and transformation of polar organic compounds is critical for accurately assessing risk to ecosystems. Laboratory-based persistence studies are used to inform regulatory decisions for chemicals but are difficult to translate to the ecosystem scale, often resulting in wide variability in predicted persistence and environmental half-lives. For example, photochemical degradation rates observed in laboratories may be orders of magnitude slower than rates observed in lakes or rivers due to differences in pathlength (i.e., water depth) and light intensity . Similarly, biodegradation rates observed in laboratories vary with inoculum source (i.e., sediment, water, or sludge) and target compound concentration, ,, making extrapolation to the environment challenging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is used to measure biodegradation by spiking the test chemical (concentrations of ≤10 μg L –1 are preferred) into aerobic natural waters or water–sediment systems with low suspended sediment concentrations (≤1 g of solids L –1 ) . However, chemical spiking has been shown to influence the microbial community and chemical attenuation, which creates doubts about the environmental relevance of the biodegradation test. , As an alternative, a nonspiked test has been suggested as it provides a better representation of biodegradation in the environment. , However, this test is constrained by the requirement for background contamination of the test chemicals in the environment of interest at quantifiable concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…They further demonstrated how the concept could be used to separate degradation half‐lives from dissipation processes in the field (a lake system; see Redman et al, 2021) and outlined its use more generally in chemical hazard and risk assessments, in particular, in calibrating and translating laboratory to field data. More recently, the same group demonstrated that comparable half‐life determinations between field‐derived and OECD TG 309 simulation tests were obtained if the tests were not spiked with a given test substance, but where biodegradation of substances in the natural waters was followed by targeted (Li & McLachlan, 2019) or nontargeted chemical analyses (Li & McLachlan, 2020). Such an approach is made possible by advances in analytical chemistry (see Specific analysis of chemicals ), but does not lend itself to new chemical substances yet to be released into the environment or those present at levels below quantification.…”
Section: Current and Future Options In Persistence Assessmentmentioning
confidence: 99%